COGNITIVE DISORDERS IN PATIENTS WITH MIGRAINE, THEIR CHARACTERISTICS AND POSSIBLE CAUSES (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Currently, migraine is one of the most common forms of primary headache. According to the results of various studies, 11-15% of the world's adult population suffers from migraine. According to data shown by a number of studies, the prevalence of migraine among the adult population of Europe has reached 14%, in China - 9.3%, in the USA - 20.2%. According to similar studies, in Russia there is also a high prevalence of migraine - 20.3% of the population, but it should be noted that a significant portion of migraine cases in domestic healthcare is often not diagnosed, which significantly distorts the idea of the prevalence of migraine in Uzbekistan. Migraine is a neurovascular disease, a primary form of headache, significantly limiting the ability of patients to work, reducing the quality of everyday life.